2017
DOI: 10.1038/s41598-017-13482-1
|View full text |Cite
|
Sign up to set email alerts
|

EEG topographies provide subject-specific correlates of motor control

Abstract: Electroencephalography (EEG) of brain activity can be represented in terms of dynamically changing topographies (microstates). Notably, spontaneous brain activity recorded at rest can be characterized by four distinctive topographies. Despite their well-established role during resting state, their implication in the generation of motor behavior is debated. Evidence of such a functional role of spontaneous brain activity would provide support for the design of novel and sensitive biomarkers in neurological diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 80 publications
4
36
0
Order By: Relevance
“…This concept has been demonstrated in a previous study using multivariate regression to model the influence of EEG frequency-band power on kinematic synergies during hand grasping (Pei et al, 2019). Another study found significant similarities between EEG microstates and muscle synergies via canonical correlation during hand reaching and grasping (Pirondini et al, 2017). To our knowledge, comparative analyses incorporating EEG and muscle synergies have not been applied to ambulation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This concept has been demonstrated in a previous study using multivariate regression to model the influence of EEG frequency-band power on kinematic synergies during hand grasping (Pei et al, 2019). Another study found significant similarities between EEG microstates and muscle synergies via canonical correlation during hand reaching and grasping (Pirondini et al, 2017). To our knowledge, comparative analyses incorporating EEG and muscle synergies have not been applied to ambulation.…”
Section: Discussionmentioning
confidence: 85%
“…Significant periods of synergy activation were marked as regions that exceeded half of the maximum temporal profile after offset subtraction and overlap were visually compared between significant ERSP modulations and synergy activations at the group level. The proposed analysis makes no assumptions regarding the type of relationship between cortical signals and synergy activations as in previously described, regression-based studies (Pirondini et al, 2017;Pei et al, 2019) and is used only as a preliminary investigation.…”
Section: Synergy-ic Overlapmentioning
confidence: 99%
“…The microstate G corresponds to the activation of the right inferior parietal lobe, extending to the superior temporal gyrus and also the cerebellum ( Khanna et al, 2015 ). Both areas are closely related to motor behavior ( Pirondini et al, 2017 ). Therefore, the appearance of microstate G after levodopa intake is strongly consistent with the improvement of motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Hence this index has been used to detect motor imagery or to indicate motor imagery performance in brain-computer interface training for stroke recovery ( 2 , 12 ). Classification techniques such as linear discriminant analysis (LDA) and support vector machines have been adopted to identify changing topographies during natural motor behaviors ( 13 ), brain state dynamics during neurodevelopment ( 14 ) and brain features during brain-computer interface control ( 15 ). An increase in classification accuracy under the same classification model after intervention may indicate an improvement in brain state transformation ability, demonstrating that different mental states can be classified more clearly and separately after training with the same classification model used.…”
Section: Introductionmentioning
confidence: 99%